Analisis Pengolahan Data Morbiditas Guna Menunjang Mutu Pelaporan Rawat Inap di Unit Rekam Medis RS Hermina Arcamanik - Wahab, Syaikhul; Humairoh, Lutfiah (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
The quality of morbidity reports in hospitals is strongly influenced by the accuracy and completeness of data recorded in the medical record system. In the digital era, the implementation of Electronic Medical Records (EMR) is expected to improve both efficiency and accuracy in reporting. However, in practice, various challenges remain, particularly to due to incomplete data entry by medical staff. This study aimed to analyze the inpatient morbidity data processing at Hermina Arcamanik Hospital and to evaluate the impact of incomplete diagnosis entries on the quality of reporting. A qualitative descriptive method was employed through in-depth interviews, observations, and surveys with medical record officers. The results showed that although the HINAI WEB system had been implemented, inconsistencies in diagnosis entry by physicians led to inaccurate morbidity data. Chronic diseases were dominant in outpatient services, while acute infections were more common in inpatient cases. Caesarean section was the most frequently performed inpatient medical procedure. The study concluded that the success of morbidity reporting is not solely determined by advanced systems, but also by the discipline and active involvement of healthcare workers in accurate and timely data documentation.